Analysis of Solar system Learning Posters Class 6 SDN Banjarsari 01 - Siti Nabila Tsalssabila (LADU: Journal of Languages and Education, 2023)
Background:  A poster is a graphic design that contains a composition of pictures and letters on large or small paper. Posters have the power to convey messages visually and with the right supporting elements, the ideas in the poster can be easily remembered by the target audience. Purpose: This study aims to determine the extent of student understanding and student success in making educational posters about learning the solar system for grade 6 SDN Banjarsari 01. Design and methods: This research used mixed analysis methods, namely qualitative and quantitative. The approach used in this research is using a mixed approach. The data collection technique was carried out by analyzing the solar system posters made by grade 6 students based on the 5 correct criteria of Schwab's poster theory. This data analysis was carried out by collecting posters that had been made by students in grade 6 at SDN Banjarsari 01. Results: Research results Based on the results of the study, it can be concluded that of the 16 posters that had been made and collected by grade 6 students at SDN Banjarsari 01 did not meet the 5 criteria of Schwab theory, only there were 7 posters that met the criteria of Schwab theory but only in the Getting attention and Showing Advantage categories, the rest only met the Getting Attention category. There are several posters that meet the conventions of poster language.